Les archives à l'ère des Big Data : les enjeux de l'archivage des données numériques massives - Ben Amor, Fatma; Mkadmi, Abderrazak (Proceedings of the 1st International Conference on Digital Tools & Uses Congress, 2018)
Big Data is now a cross-cutting research topic in all disciplines related to digital as content and as technology too. They lie in the intersection between all the massive data captured, obtained, created by different means and of various origins. They represent an advanced step in the re-development of information, particularly concerning data management and data retention issues. This upheaval due to these massive data has touched all sectors, particularly the archives. Indeed, given their volume, their speed of creation and their importance to the social, economic, scientific and cultural actors, the sorting, the treatment and the conservation of these data Massive e orts require memory capacity, new methods and techniques for processing, analyzing and managing particular flows. We will try in this article to bring some elements of primary answers on the modalities of generative multiplication. exponential of numerical data and archive in a mass of numeric data, data that are in flux and that occur in a sup speed.

Archiver les Big Data : un enjeu pour l'archiviste d’aujourd'hui et de demain ? - Vieira, Alexandre (Enssib, 2018)